2023
DOI: 10.1111/polp.12538
|View full text |Cite
|
Sign up to set email alerts
|

You'll never walk alone: Loneliness, religion, and politico‐economic transformation

Abstract: The rise of subversive religious beliefs has been recently documented as related to the politico‐economic radicalization of places that feel left behind. When is the traditional local religious institution so socio‐economically inefficient in providing hope for “not walking alone” to become substituted by subversive religious beliefs on the market for hope? This article suggests a detailed methodology, linking micro and macro levels, that starts from the quantification of the individual gain from religion as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Other studies have also documented the electoral consequences of irrational beliefs. For instance, Tubadji (2022) showed that voters who believe in subversive narratives and, for instance, identify themselves as witches voted disproportionally in favor of Brexit. Several studies have confirmed that neo-paganism in general, and Odinism in particular, represent a fertile ground in which neo-Nazi ideas and movements can flourish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also documented the electoral consequences of irrational beliefs. For instance, Tubadji (2022) showed that voters who believe in subversive narratives and, for instance, identify themselves as witches voted disproportionally in favor of Brexit. Several studies have confirmed that neo-paganism in general, and Odinism in particular, represent a fertile ground in which neo-Nazi ideas and movements can flourish.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies have highlighted the political consequences of a traditional mindset in several countries from the Global South, they nevertheless have little to say as to whether having a traditional mindset and, for example, believing in fortune tellers, horoscopes, or lucky charms also has certain political implications for countries in the Global North-where what have alternatively been labeled as new religions, cults, or, in our words, "traditional beliefs" have become more common and may possibly have expanded political consequences (Tubadji 2022).…”
mentioning
confidence: 90%
See 1 more Smart Citation